The Origins of Tell Leilan and the Conquest of Space in Third Millennium Mesopotamia - Weiss, Harvey
Modern and Ancient Land Use — Irrigation Agriculture in Northern Mesopotamia — Third Millennium Urbanization on the Habur Plains — Eannatum and Subir — Preliminary Survey of the Tell Leilan Sustaining Area